Poverty and its reduction in a Chinese border region: is social capital important?. Issue 1 (2nd January 2019) - Hong, Liu; Tisdell, Clem; Fei, Wang
Abstract: China is trying to reduce the high levels of poverty in its border regions, dominated by ethnic minorities. To do so, it is giving particular attention to increasing physical and human capital but not social capital. This article investigates the extent to which social capital (and other variables) are associated with the absence of poverty in such regions. To this end, data were collected from a sample of households in the Kirghiz Prefecture of Xinjiang and analyzed using logistic regression analysis and other methods. Some components of social capital and some other variables show a significant association with the absence of poverty. However, care is needed in applying the results because association must not be confused with causality. Limited opportunities exist for productive investment in the border regions considered. Several issues raised are also relevant to remote (ethnic) communities outside of China. The government's scope for altering social capital is assessed.